Quaternized asymmetric branched polyaryl piperidine as well as preparation method and application thereof
By introducing quaternized asymmetric branched polyaryl piperidine with rigid and flexible branched units into the anion exchange membrane, the problems of attenuation of mechanical properties and poor chemical stability of branched polymers are solved, and high ion conductivity and mechanical performance improvements are achieved under high temperature and high alkaline conditions.
Patent Information
- Application Number
- CN202510673571.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-09-05
AI Technical Summary
In the existing anion exchange membrane fuel cells, branched polymers have problems such as attenuation of mechanical properties, poor processability and decreased conductivity. At the same time, alkaline membranes have poor chemical stability under high temperature and strong alkaline conditions, making it difficult to improve ion conductivity and mechanical properties at the same time.
Using quaternized asymmetric branched polyaryl piperidine, a film material with excellent alkali resistance and high ion conductivity was prepared by introducing rigid branched unit fluorenyl and flexible branched unit phenyl into the polymer, combined with quaternization reaction.
It is achieved to improve the mechanical properties and ion conductivity of the film under high temperature and strong alkaline conditions, enhance the alkali resistance and processability of the film, and improve the overall performance of the film.
Smart Images

Figure CN120590611A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a quaternized asymmetric branched polyaryl piperidine and a preparation method and application thereof. Background Art
[0002] Developing anion exchange membranes with high electrical conductivity, mechanical stability, and alkali resistance is a key research priority in anion exchange membrane fuel cells (ANEMFs). However, there is a conflict between membrane conductivity and stability. Studies have shown that the branched structure of typical symmetrically branched anion exchange membranes reduces the regularity of the molecular chains, leading to weakened chain entanglement and increased interchain distances. This in turn creates numerous micropores, resulting in a higher fractional free volume (FFV), significantly reducing ion transport resistance. Branched polymers not only promote the formation of microphase separation structures, reducing ion transport resistance, but also contribute to the formation of branched networks, improving membrane dimensional stability and mechanical properties. However, due to their symmetrical, highly rigid or non-rigid internal structures, branched polymers can suffer from reduced mechanical properties, poor processability, or excessive chain accumulation, leading to decreased conductivity.
[0003] At the same time, under the high temperature (60°C) and strong alkaline (pH>14) operating conditions of alkaline anion exchange membrane fuel cells (AEMFCs), the chemical stability of poly(arylene ether) backbones is poor. Especially when the backbone contains electron-withdrawing groups (such as sulfone groups), the ether oxygen bond is easily hydrolyzed and cleaved. Preparing poly(arylene hydrocarbon) polymers without aryl ethers is an effective method to address the poor alkaline stability of polymer materials.
[0004] Research has shown that polyarylpiperidine polymers synthesized via superacid catalysis, due to their lack of ether bonds and their unique ring strain and conformational constraints, significantly increase the transition state energy for both elimination and nucleophilic substitution degradation, thereby greatly improving their alkali resistance. However, there is also a conflict between the high ionic conductivity and excellent mechanical properties of these alkaline membranes. Summary of the Invention
[0005] The present invention aims to provide a quaternized asymmetric branched polyaryl piperidine, a preparation method and application thereof. When the quaternized asymmetric branched polyaryl piperidine prepared by the preparation method provided by the present invention is used in an anion exchange membrane, it can simultaneously improve the ion conductivity and mechanical properties of the membrane and has excellent alkali resistance and stability.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a quaternized asymmetric branched polyarylpiperidine having a structure shown in Formula I:
[0008] n is 1 to 30%;
[0009] In formula I, Ar includes
[0010]
[0011] The present invention provides a method for preparing the quaternized asymmetric branched polyarylpiperidine described in the above technical solution, comprising the following steps:
[0012] Aromatic compounds, N-methyl-4-piperidone and 9,9-diphenylfluorene are polymerized under strong acid catalysis to obtain an asymmetrically branched polymer.
[0013] quaternizing the asymmetrically branched polymer with a halogenated hydrocarbon to obtain a quaternized asymmetrically branched polyarylpiperidine;
[0014] The aromatic compounds include
[0015]
[0016] Preferably, the molar ratio of the aromatic compound to 9,9-diphenylfluorene is 70:30 to 99:1.
[0017] Preferably, the strong acid includes trifluoroacetic acid and trifluoromethanesulfonic acid; and the molar ratio of the aromatic compound to the strong acid is 1:9 to 1:11.
[0018] Preferably, the molar ratio of the asymmetrically branched polymer to the halogenated hydrocarbon is 1:1 to 1:5.
[0019] Preferably, the temperature of the quaternization reaction is 25 to 80° C., and the insulation time is 24 to 48 hours.
[0020] Preferably, the polymerization reaction is carried out in an ice bath for 4 to 8 hours.
[0021] The present invention also provides the use of the quaternized asymmetric branched polyaryl piperidine described in the above technical solution or the quaternized asymmetric branched polyaryl piperidine prepared by the above preparation method in an anion exchange membrane of a fuel cell.
[0022] The present invention also provides an anion exchange membrane, which is obtained by casting a solution of quaternized asymmetric branched polyarylpiperidine into a membrane and then subjecting it to alkaline solution ion exchange;
[0023] The quaternized asymmetrically branched polyaryl piperidine is the quaternized asymmetrically branched polyaryl piperidine described in the above technical solution or the quaternized asymmetrically branched polyaryl piperidine prepared by the above preparation method.
[0024] Preferably, the concentration of the alkali solution is 0.5-2 mol / L.
[0025] The present invention provides a quaternized asymmetric branched polyarylpiperidine having a structure shown in Formula I:
[0026]
[0027] In formula I, n is 1 to 30%;
[0028] In formula I, Ar is
[0029]
[0030] The quaternized asymmetric branched polyaryl piperidine of the present invention has the following advantages when used as a membrane: The present invention introduces a rigid branching unit fluorenyl group into the polymer to increase the free volume fraction of the membrane, reduce ion transport resistance, and improve the mechanical properties of the membrane (made of the quaternized asymmetric branched polyaryl piperidine). At the same time, phenyl groups (provided by 9,9-diphenylfluorene) are introduced into the quaternized asymmetric branched polyaryl piperidine, which are connected to the fluorenyl group through a single structure to form a flexible branching unit, thereby reducing the attenuation of its mechanical properties and improving its processability. In addition, the annular molecular conformation induced by the branching structure of the quaternized asymmetric branched polyaryl piperidine increases the transition state energy for degrading or nucleophilic substitution degradation, thereby improving the alkali stability of the membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0032] Figure 1 This is the H NMR spectrum of poly(terphenylpiperidine) and 1-PTDP-2.5;
[0033] Figure 2 I is the 1-PTDP-2.5 prepared in Application Example 1 - Mechanical properties and thermal stability diagram of the molded film;
[0034] Figure 3 OH of QPTP and 1-QPTDP-2.5 - Microphase morphology of type branched membrane;
[0035] Figure 4 is the incremental pore volume and pore size distribution of type I membranes of QPTP and 1-QPTDP-2.5;
[0036] Figure 5 OH of QPTP and 1-QPTDP-2.5 films at different temperatures - conductivity graph;
[0037] Figure 6 These are the H NMR spectra of PBDP-2.5 and QPBDP-2.5. DETAILED DESCRIPTION
[0038] The present invention provides a quaternized asymmetric branched polyarylpiperidine having a structure shown in Formula I:
[0039] n is 1 to 30%;
[0040] In formula I, Ar includes
[0041]
[0042]
[0043] The present invention also provides a method for preparing the quaternized asymmetric branched polyarylpiperidine described in the above technical solution, comprising the following steps:
[0044] Aromatic compounds, N-methyl-4-piperidone and 9,9-diphenylfluorene are polymerized under strong acid catalysis to obtain an asymmetrically branched polymer.
[0045] quaternizing the asymmetrically branched polymer with a halogenated hydrocarbon to obtain a quaternized asymmetrically branched polyarylpiperidine;
[0046] The invention conducts polymerization reaction on aromatic compounds, N-methyl-4-piperidone and 9,9-diphenylfluorene under strong acid catalysis conditions to obtain an asymmetric branched polymer.
[0047] As an embodiment of the present invention, the aromatic compound may include the aromatic compound includes
[0048] As an embodiment of the present invention, the molar ratio of the aromatic compound to 9,9-diphenylfluorene may be 70:30 to 99:1.
[0049] As an embodiment of the present invention, the strong acid may include trifluoroacetic acid and trifluoromethanesulfonic acid; the molar ratio of the trifluoroacetic acid to the trifluoromethanesulfonic acid may be 1:9 to 1:11, specifically 1:10. As an embodiment of the present invention, the molar ratio of the aromatic compound to the strong acid may be 1:9 to 1:11, specifically 1:10.
[0050] In the present invention, setting the ratio of the strong acid and the ratio of the strong acid to the aromatic compound to the above ratios can completely protonate N-methyl-4-piperidone to form an active intermediate to promote the smooth progress of the polymerization reaction.
[0051] As an embodiment of the present invention, the polymerization reaction is carried out in an ice bath, specifically at 0°C, for 4 to 8 hours, specifically 4 to 5 hours. As an embodiment of the present invention, the polymerization reaction is accompanied by stirring, and the stirring can be magnetic rotor stirring.
[0052] As an embodiment of the present invention, when the polymerization reaction is completed, the mixture after the polymerization reaction is poured into a potassium carbonate solution to quench the polymerization reaction, and the precipitated white solid is washed with deionized water and dried to obtain an asymmetrically branched polymer.
[0053] After obtaining the asymmetrically branched polymer, the present invention conducts a quaternization reaction between the asymmetrically branched polymer and a halogenated hydrocarbon to obtain a quaternized asymmetrically branched polyarylpiperidine.
[0054] As an embodiment of the present invention, the halogenated hydrocarbon may be an iodinated alkane or a brominated alkane; the iodinated alkane may be methyl iodide; the brominated alkane may be 1-bromohexane or 1-bromocyclohexane.
[0055] As an embodiment of the present invention, the molar ratio of the asymmetrically branched polymer to the halogenated hydrocarbon may be 1:1 to 1:5, specifically 1:1, 1:2, 1:3, 1:4, 1:4.21 or 1:5.
[0056] As an embodiment of the present invention, the temperature of the quaternization reaction can be 25-80°C, specifically 30°C, 40°C, 50°C, 60°C or 70°C, and the insulation time can be 24-48h, specifically 25h, 30h or 40h.
[0057] The present invention also provides the use of the quaternized asymmetric branched polyaryl piperidine described in the above technical solution or the quaternized asymmetric branched polyaryl piperidine prepared by the preparation method described in the above technical solution in an anion exchange membrane for a fuel cell.
[0058] The present invention also provides an anion exchange membrane, which is obtained by casting a solution of quaternized asymmetric branched polyaryl piperidine into a membrane and then subjecting it to alkaline solution ion exchange; the quaternized asymmetric branched polyaryl piperidine is the quaternized asymmetric branched polyaryl piperidine described in the above technical solution.
[0059] When the quaternized asymmetric branched polyarylpiperidine in the present invention is used as an anion exchange membrane, since its molecule contains both rigid units and flexible units, the mechanical properties of the membrane can be balanced. At the same time, the introduction of the rigid branched unit fluorene group increases the free volume fraction of the membrane, reduces the ion transport resistance, and thus improves the ion conductivity.
[0060] In one embodiment of the present invention, the anion exchange membrane is formed by casting a quaternized asymmetric branched polyarylpiperidine solution into a membrane and then subjecting it to ion exchange with an alkaline solution. In one embodiment of the present invention, the alkaline solution includes a KOH solution or a NaOH solution; the concentration of the alkaline solution can be 0.5 to 2 mol / L, specifically 1 mol / L.
[0061] In order to further illustrate the present invention, the scheme of the present invention is described in detail below with reference to the accompanying drawings and embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0062] Example 1
[0063] Preparation of 9,9-diphenylfluorene-branched polyterphenylpiperidine: The branching degree n is 2.5%, where 2.5% means that 9,9-diphenylfluorene accounts for 2.5% of the total amount of p-terphenyl and 9,9-diphenylfluorene.
[0064] p-Terphenyl (2.25 g, 9.75 mmol), 9,9-diphenylfluorene (80 mg, 0.25 mmol), and N-methyl-4-piperidone (1.28 mL, 11 mmol) were added to a round-bottom flask containing 15 mL of dichloromethane and stirred at 0°C for 30 min. Trifluoroacetic acid (0.82 mL, 11 mmol) and trifluoromethanesulfonic acid (9.8 mL, 110 mmol) were then slowly added sequentially to initiate the reaction. The reaction was stirred throughout and maintained at 0°C. During the reaction, the solution color changed from light yellow to dark blue. After 4.5 h, the solution viscosity reached its maximum, resulting in rotor obstruction, signaling the end of the reaction.
[0065] The solution was poured into 300 mL of 10 wt% potassium carbonate solution for quenching, and the precipitated white solid product was collected, washed with deionized water until neutral and dried at 60° C. to obtain a polymer with a branching degree of 2.5%, which was named 1-PTDP-2.5.
[0066] In a clean flat-bottom flask, PTDP-2.5 (1.2 g, 3.8 mmol) was dissolved in 20 mL of dimethyl sulfoxide (DMSO) containing 0.4 mL of trifluoroacetic acid. Potassium carbonate (1.52 g, 11 mmol) was then added. After stirring for 15 minutes, iodomethane (1 mL, 16 mmol) was added and the mixture was allowed to react at 30°C in the dark for 48 hours. After the reaction, the solution was slowly poured into 300 mL of ethyl acetate to precipitate a white powder. The powder was washed with deionized water until neutral and dried to obtain a pale yellow product, which was named 1-QPTDP-2.5.
[0067] Example 2
[0068] The difference from Example 1 is the degree of branching, wherein the molar amount of 9,9-diphenylfluorene added during the preparation is 2.25 mol, and the final product prepared is recorded as 2-QPTDP-18.75.
[0069] Example 3
[0070] Biphenyl (2.25 g, 9.75 mmol), 9,9-diphenylfluorene (80 mg, 0.25 mmol), and N-methyl-4-piperidone (1.28 mL, 11 mmol) were added to a round-bottom flask containing 15 mL of dichloromethane and stirred at 0°C for 30 min. Trifluoroacetic acid (0.82 mL, 11 mmol) and trifluoromethanesulfonic acid (9.8 mL, 110 mmol) were then slowly added sequentially to initiate the reaction. The reaction was stirred throughout and maintained at 0°C. During the reaction, the solution color changed from light yellow to dark blue. After 4.5 h, the solution viscosity reached its maximum, resulting in rotor obstruction, signaling the end of the reaction.
[0071] The solution was poured into 300 mL of 10 wt% potassium carbonate solution to quench, and the precipitated white solid product was collected, washed with deionized water until neutral and dried at 60° C. to obtain a polymer with a branching degree of 2.5%, which was named PBDP-2.5.
[0072] In a clean flat-bottom flask, PBDP-2.5 (1.2 g, 3.8 mmol) was dissolved in 20 mL of dimethyl sulfoxide (DMSO) containing 0.4 mL of trifluoroacetic acid. Potassium carbonate (1.52 g, 11 mmol) was then added. After stirring for 15 minutes, iodomethane (1 mL, 16 mmol) was added and the mixture was allowed to react at 30°C in the dark for 48 hours. After the reaction, the solution was slowly poured into 300 mL of ethyl acetate to precipitate a white powder. The white powder was washed with deionized water until neutral and dried to obtain a pale yellow product, which was named QPBDP-2.5.
[0073] Application Example 1
[0074] 0.4 g of 1-QPTDP-2.5 was dissolved in 15 mL of DMSO to prepare a 2.67% (w / v) casting solution. Impurities were then filtered using a 0.45 μm polytetrafluoroethylene (PTFE) filter. The filtered solution was poured onto a clean glass plate and dried at 80°C for 24 h under vacuum to remove the solvent DMSO. After complete drying, the membrane (denoted as I of 1-QPTDP-2.5) was placed on a clean glass plate. - The membrane was taken out and immersed in 1 mol / L NaOH solution at 80 ° C for 24 h to complete the ion exchange. Then, the residual alkali solution on the membrane surface was fully washed with nitrogen-saturated deionized water to obtain 1-QPTDP-2.5 OH - The membrane was stored under nitrogen protection.
[0075] Application Example 2
[0076] The only difference from Application Example 1 is that 1-QPTDP-2.5 is replaced by 2-QPTDP-18.75.
[0077] Application Example 3
[0078] The only difference from Application Example 1 is that 1-QPTDP-2.5 is replaced by 2-QPTDP-2.5.
[0079] Figure 1 The following are the H-NMR spectra of poly(terphenylpiperidine) (PTP) and 1-PTDP-2.5. The testing process is as follows:
[0080] 25 mg of poly(terphenylpiperidine) (PTP) and 25 mg of 1-PTDP-2.5 were dissolved in 0.6 mL of deuterated dimethyl sulfoxide (DMSO-d6) containing 5 vol% trifluoroacetic acid (TFA). 1H NMR spectra of the samples were acquired on a Bruker Plus 600 MHz spectrometer with a resonance frequency of 600 MHz, using tetramethylsilane (TMS) as the internal standard. The addition of TFA not only facilitates polymer dissolution but also shifts the water peak, allowing the peak of the piperidine ring to be observed.
[0081] according to Figure 1 It can be seen that when protonated with TFA, the N on the piperidine ring of PTP and 1-PTDP-2.5 polymers is protonated, and the NH on the protonated piperidinium group (Hg) appears at 9.73 ppm. Both show aromatic H (H a ,H b ,H c ), however, a new set of signals (H h , H i, H j ), which can be attributed to the H signal of 9,9-diphenylfluorene unit, indicating the successful synthesis of 1-PTDP-2.5. In addition, at 2-4ppm, both showed the signal peak of piperidine ring H. Due to the addition of TFA, H d , H e The signal at 1.57 ppm was split, and new signal peaks were formed at 2.32 ppm and 3.22 ppm.
[0082] Figure 6 These are the H NMR spectra of PBDP-2.5 and QPBDP-2.5.
[0083] The OH of 1-QPTDP-2.5 prepared in Application Example 1 was tested by back titration. - The ion exchange capacity (IEC) of a branched membrane is determined as follows:
[0084] 1-QPTDP-2.5 OH - The branched membrane was cut into pieces and soaked in 0.01mol / L HCl solution at 30℃ for 72h. Then a certain volume of solution was taken and titrated with 0.01mol / LNaOH solution to calculate the amount of HCl after soaking. Subsequently, the membrane sample was rinsed with deionized water until neutral, dried in a vacuum drying oven at 60℃ for 24h, and the mass (m) of the dry membrane was weighed. Phenolphthalein was used as an indicator to determine the titration end point during the titration process. The IEC of the branched membrane (mmol·g) was calculated according to formula (1) -1 ).
[0085]
[0086] In formula (1), M b,HCl The amount of HCl used to soak the branched membrane; M a,HCl is the amount of HCl remaining in the soaking solution; m is the mass of the dry branched membrane in the experiment.
[0087] The IEC of 1-QPTDP-2.5 membrane was found to be 2.86 mmol·g -1 , which is greater than the IEC of QPTP film (IEC QPTP =2.56mmol·g -1 ).
[0088] 1-QPTDP-2.5I - The tensile strength and elongation at break of the film were measured by a tensile testing machine. The test process was as follows: QPTP and 1-QPTDP-2.5 - The molded film was cut into 1cm×4cm strips and dried at 1mm·min -1 The tensile rate was tested. The results are as follows Figure 2 Shown in a: I of 1-QPTDP-2.5 - The tensile strength of the membrane was improved, and the elongation at break increased from 15.36% of QPTP to 20.26% of 1-QPTDP-2.5, proving that 9,9-diphenylfluorene can indeed improve the mechanical properties of the membrane to a certain extent.
[0089] 1-QPTDP-2.5I - The thermal stability of the film was measured by a synchronous thermal analyzer. The test process was as follows: a 3 mm × 3 mm 1-QPTDP-2.5 I - The membrane was heated at 10℃·min in nitrogen atmosphere. -1 The sample was heated from 30°C to 800°C at a heating rate of 1.5 %. The test results are shown in Figure 2 Middle b, from Figure 2 As can be seen in b, the thermal stability of 1-QPTDP-2.5 is better than that of the unbranched QPTP membrane.
[0090] The 1.5wt% concentration of the membrane (the membrane material is 1-QPTDP-2.5 OH - The 1-QPTDP-2.5 (branched membrane and QPTP) solution was dropped onto a copper grid and TEM images of the membrane were obtained using a JEOL JEM-F200 transmission electron microscope. The OH groups of 1-QPTDP-2.5 (1.5 cm × 1.5 cm) were observed using a Bruker DimensionIcon atomic force microscope (AFM) phase image. - The microphase morphology of the branched membrane. Figure 3 As shown in the figure, the bright area belongs to the hydrophobic area formed by the polymer skeleton, and the dark area belongs to the hydrophilic area generated by the self-aggregation of cations and water molecules. It can be clearly seen that the OH groups of 1-QPTDP-2.5 - The more and larger ion clusters appear in the asymmetric branched membrane, which means that the asymmetric branched membrane has a more obvious hydrophilic / hydrophobic phase separation morphology, which is beneficial to OH - transmission.
[0091] The CO2 adsorption performance of branched and unbranched membranes was analyzed at 0°C using a Micromeritics TristarⅡ3020 fully automatic specific surface and porosity analyzer (BET). Before testing, the I-type membranes were degassed at 120°C under vacuum for 12 h. The incremental pore volume and pore size distribution of the I-type membranes of QPTP and 1-QPTDP-2.5 were measured as follows: Figure 4 As shown in the Figure 3, it can be clearly seen that when the pore size is less than 0.5 nm, the type I membrane of 1-QPTDP-2.5 has a higher incremental pore volume, which indicates that it has better microporous performance.
[0092] The OH of 1-QPTDP-2.5 was measured by four-point probe electrochemical impedance spectroscopy in the range of 1 Hz to 100 kHz on an electrochemical workstation. - OH of branched membrane - Conductivity (σ). - The branched membrane was cut into 0.9 cm × 3.5 cm strips and completely immersed in deionized water passing through N2 during the test. The test system was heated in a water bath and the membrane resistance was measured at 30-60°C. The ionic conductivity was calculated as shown in formula (2):
[0093]
[0094] In formula (2), L is the distance between the two platinum wire electrodes (cm); d is the thickness of the membrane (cm); w is the width of the membrane (cm); and R is the measured membrane resistance (mΩ).
[0095] The OH groups of QPTP and 1-QPTDP-2.5 measured at different temperatures - OH of branched membrane - Conductivity Figure 5 As shown. Figure 5 It can be seen that the OH of QPTP and 1-QPTDP-2.5 - The conductivity of the branched membranes increased with the increase of temperature, especially the OH of 1-QPTDP-2.5. - The conductivity of the branched membrane at 30℃ is 72.53mS·cm -1 , which is only lower than the conductivity of QPTP membrane at 60℃, which is 75.63mS·cm -1 It is 4.10% lower than that of the conventional catalyst, showing a considerable improvement in electrical conductivity, which can be attributed to its enhanced microphase separation structure and microporous properties.
[0096] In summary, this type of branched anion exchange membrane has better performance than the unbranched membrane, not only improving the mechanical and thermodynamic properties, but also improving the IEC and OH - The electrical conductivity is also significantly improved, showing its potential for use in alkaline fuel cells.
[0097] Although the above embodiment provides a detailed description of the present invention, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A quaternized asymmetric branched polyarylpiperidine, characterized in that Having the structure shown in formula I: n is 1 to 30%; In formula I, Ar includes 2. The method for preparing the quaternized asymmetrically branched polyarylpiperidine according to claim 1, comprising the steps of: Aromatic compounds, N-methyl-4-piperidone and 9,9-diphenylfluorene are polymerized under strong acid catalysis to obtain an asymmetrically branched polymer. quaternizing the asymmetrically branched polymer with a halogenated hydrocarbon to obtain a quaternized asymmetrically branched polyarylpiperidine; The aromatic compounds include 3. The preparation method according to claim 2, wherein The molar ratio of the aromatic compound to 9,9-diphenylfluorene is 70:30 to 99:
1.
4. The preparation method according to claim 2 or 3, wherein The strong acid includes trifluoroacetic acid and trifluoromethanesulfonic acid; the molar ratio of the aromatic compound to the strong acid is 1:9 to 1:
11.
5. The preparation method according to claim 2, wherein The molar ratio of the asymmetrically branched polymer to the halogenated hydrocarbon is 1:1 to 1:
5.
6. The preparation method according to claim 2, wherein The temperature of the quaternization reaction is 25-80° C., and the insulation time is 24-48 hours.
7. The preparation method according to claim 2 or 3, characterized in that The polymerization reaction is carried out in an ice bath for 4 to 8 hours.
8. Use of the quaternized asymmetric branched polyarylpiperidine according to claim 1 or the quaternized asymmetric branched polyarylpiperidine prepared by the preparation method according to any one of claims 2 to 7 in anion exchange membranes for fuel cells.
9. An anion exchange membrane, characterized in that The anion exchange membrane is obtained by casting a solution of quaternized asymmetric branched polyarylpiperidine into a membrane and then subjecting it to alkaline solution ion exchange; The quaternized asymmetrically branched polyaryl piperidine is the quaternized asymmetrically branched polyaryl piperidine according to claim 1 or the quaternized asymmetrically branched polyaryl piperidine prepared by the preparation method according to any one of claims 2 to 7.
10. The anion exchange membrane according to claim 9, characterized in that The concentration of the alkali solution is 0.5-2 mol / L.